THE ROLE OF ARTIFICIAL INTELLIGENCE IN CYBER SECURITY: the use of intelligent systems for the benefit of corporate data security. - Pagim Zequim, Eduarda; Francisco Ribeiro, Douglas (Revista Interface Tecnológica, 2022)
Present in the routine of most people and especially in organizations, technology has been the main responsible for solving problems in an intelligent way, but its improper use can open space for breaches in the organization's systems, causing malicious attacks and coming causing large-scale damage. With that, this work aims to present how Artificial Intelligence is important for large, medium and small organizations, helping mainly in the identification of malicious attacks and thus reinforcing information security.
Keywords: information security; artificial intelligence in companies; hacker attack